Making sense of students' attitude towards college general chemistry: A partial least squares structural equation modeling (PLS-SEM) approach - Denson Liday (Journal of Technology and Science Education, 2025)
Understanding students' attitudes towards college general chemistry is crucial for improving chemistry education and enhancing students' learning experiences. This study investigates student attitudes towards college general chemistry and their impact on academic performance. Descriptive results unveiled an overall negative attitude (µ=2.62), linked to factors like perceived difficulty, relevance, past experiences, societal influences, and learning style variations. To address this challenge, recommendations were made, advocating improved teaching methods, supportive learning environments, bias awareness, personalized instruction, and positive chemistry experiences. Inferential statistics identified distinct negative attitudes within constructs, with Interest and Utility displaying the highest negativity (μ=2.853). These findings underscore the importance of engaging teaching strategies and highlighting the practical applications of chemistry to boost student attitudes and engagement. Additionally, profile variables like the SHS strand and academic standing significantly influenced attitude constructs, indicating the need for tailored instructional approaches and support for students from diverse backgrounds. Structural Equation Modeling (SEM) exposed direct links among attitude constructs, emphasizing the role of interest, perceived usefulness, and emotional satisfaction in shaping student attitudes and engagement. The PLS-SEM technique was used to test the measurement and structural models (3 dimensions, 8 elements, 21 constructs, and 27 hypotheses). In addition, 11 hypotheses from the 3 dimensions of 8 elements have a positive and significant effect. Notably, SEM showed that emotional satisfaction (p value=<.001) and anxiety (p value=<.001) directly impact general chemistry academic performance. Therefore, creating a positive, supportive learning environment and addressing anxiety through stress management techniques are vital for improved academic outcomes.